Influence of spraying parameters on the electrochemical behaviour of HVOF thermally sprayed stainless steel coatings in 3.4% NaCl - Guilemany, J. M.; Fernandez, J.; Espallargas, N.; Suegama, P. H.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2006)
Stainless steel coatings obtained by High Velocity Oxygen Fuel (HVOF) were characterized using optical (OM) and scanning electron microscopy (SEM), electron probe micro-analysis, X-ray diffraction (XRD), open-circuit potential (E-OC) measurements, electrochemical impedance spectroscopy (EIS) and polarisation tests. Differences among coated steels were mainly related with the gun-substrate distance parameter (310 nm for samples A and B and 260 min for C and D). The open-circuit potential values measured for all the samples after 18 h of immersion in aerated and unstirred 3.4% NaCl solution were: - 0.334, - 0.360, - 0.379 and - 0.412 V vs. Ag/AgCl,KClsat. for samples A to D, respectively. For EIS measurements, Nyquist plots showed higher capacitive semi-circle for samples sprayed at longer distance, indicating higher corrosion resistance in NaCl solution. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: HVOF; stainless steel; thermal spraying; corrosion; electrochemical behaviour